Long-Term Socioeconomic and Neurologic Outcome for Individuals with Childhood-Onset Multiple Sclerosis - Moritz Tacke; Iris Hannibal; Katharina Vill; Michaela V. Bonfert; Wolfgang Müller-Felber; Astrid Blaschek (MDPI AG, 2024)
Intorduction: Most studies on the progression of childhood-onset multiple sclerosis (MS) involve relatively short follow-up periods, focusing primarily on neurological outcomes and disability progression. The influence of these and other factors on the health-related quality of life is not known. To gain a comprehensive understanding of early-onset MS, it is crucial to evaluate the effects of treatment and the disease on quality of life. Method: This pilot project aimed to evaluate the feasibility of using an online survey tool for long-term follow-up data collection from patients with childhood-onset MS. An anonymized, monocentric, prospective survey was conducted on a convenience cohort of patients treated at a certified centre for neuromuscular diseases in childhood between 2007 and 2019. Results: A total of 27 patients completed the survey. There were no mandatory items, therefore some patients chose not to answer all the questions in the questionnaire. Patients exhibited promising educational achievements, low neurological disease burden, and high resilience. However, anxiety, depression, and pain significantly impacted their perceived health status. Conclusion:This single-centre study has yielded new insights into childhood-onset MS. To enable more accurate comparisons across different centres and countries, it is essential to establish a minimum data set and questionnaire subset for patients with paediatric-onset MS transitioning into adulthood.